The Validity of Go-Lab Platform-assisted, Character Value-Integrated Causalitic Model Learning Tools to Enhance Problem-Solving and Creative Thinking Skills - Kosim, Kosim; Mahmudah, Huraiza; Rokhmat, Joni (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2023)
This research aims to determine the validity of the causalistic model learning tool integrated with the rocky character values of the Go-Lab platform to improve students' problem-solving and creative thinking abilities. This type of research is research development or Research and Development (RnD). This development research procedure refers to the steps of the 4D development model, which consists of four main stages: define, design, develop, and disseminate. The causalistic model learning tools integrated with the Go-Lab platform's rocky character values were developed in the form of a syllabus, learning implementation plan (RPP), teaching materials, student worksheets, Go-Lab platform media, as well as problem-solving and creative thinking ability test instruments. The results of this research are that the causalistic model learning tool integrated with the rocky character values of the Go-Lab platform is valid for use in science learning to improve students' problem-solving and creative thinking abilities.